Implementasi Kurikulum PAI Adiwiyata Berbasis Teknologi: Kajian TPACK dan UNESCO Tbilisi di SD Bakalan: Adiwiyata - Annisa Qibti Nur’Aini (Jurnal Pendidikan Agama Islam, 2026)
This study aims to describe the implementation of an Adiwiyata-based Islamic Religious Education (IRE) curriculum supported by technology through the TPACK (Technological Pedagogical and Content Knowledge) framework and the UNESCO Tbilisi principles at SD Negeri Bakalan. This research employed a qualitative approach using field research methods. Data were collected through observations, in-depth interviews with IRE teachers and the Adiwiyata coordinator, and documentation. Data analysis was conducted using descriptive qualitative techniques involving data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the adiwiyata based IRE curriculum at SD Negeri Bakalan has been carried out effectively and holistically. The integration of Islamic values with environmental issues is realized through the use of interactive learning technologies and the application of the TPACK model, which encompasses content mastery, contextual pedagogical strategies, and digital media utilization. Furthermore, the UNESCO Tbilisi principles awareness, knowledge, attitudes, skills, and participation—have been successfully implemented in IRE learning and school culture. This implementation contributes to the development of students’ religious character and environmental awareness through habitual environmentally friendly behaviors and active participation in adiwiyata programs. Therefore, technology-supported adiwiyata based IRE learning can serve as an effective model for fostering sustainable environmental care attitudes among students.